Pengaruh Tingkat Pemahaman Terhadap Hasil Belajar Mata Pelajaran Akuntansi Pada Siswa Kelas X Di SMK Negeri 1 Kota Bengkulu - Sazili, Sazili; Selviani, Ayudho; Handayani, Mely (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to determine whether there is an effect of accounting. This study used quantitative methods. The population in this study were students of Class X accounting expertise program SMK Negeri 1 Kota Bengkulu, with a sample of 41 students determined through Strativied Sampling technique. This data collection technique is done through questionnaires and documentation of final Semester exam scores. The results of the analysis showed that the level of student understanding is in the category of